2019
DOI: 10.1016/j.omtn.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Circulating lncRNA BC030099 Increases in Preeclampsia Patients

Abstract: Long noncoding RNAs (lncRNAs) have increasingly been shown to be important biological regulators involved in numerous diseases. Further, increasing evidence demonstrates that circulating lncRNAs can be used as diagnostic biomarkers. Therefore, the purpose of this study was to evaluate the potential for circulating lncRNAs as novel biomarkers for the diagnosis of preeclampsia. In the present study, we measured the expression of five lncRNAs known to be relevant to the uterus in whole blood samples from 48 preec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…With the development of next-generation sequencing, cell-free noncoding RNAs are attracting much attention as promising molecular biomarkers [34]. miRNAs, long noncoding RNAs, and circular RNAs are the focus of many clinical studies aimed at detecting common pregnancy complications, such as gestational diabetes [35,36] and preeclampsia [37,38]. However, no studies have reported the use of piRNAs as potential prenatal biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of next-generation sequencing, cell-free noncoding RNAs are attracting much attention as promising molecular biomarkers [34]. miRNAs, long noncoding RNAs, and circular RNAs are the focus of many clinical studies aimed at detecting common pregnancy complications, such as gestational diabetes [35,36] and preeclampsia [37,38]. However, no studies have reported the use of piRNAs as potential prenatal biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al showed that levels of lncRNA BC030099 in whole blood had a good ability to discriminate preeclamptic from healthy pregnant women (AUC = 0.713). Furthermore, lncRNAs NR_026824.1, AK055151.1, NR_027457, and NR_024178 were highly upregulated in PE placentas but did not demonstrate good biomarker potential for PE (AUC < 0.6) [ 145 ]. Luo et al suggested that levels of three lncRNAs in serum AF085938, G36948, and AK002210 can also serve as potential diagnostic biomarkers in preeclampsia (AUC = 0.7673, 0.7956, and 0.7575, respectively) [ 146 ].…”
Section: Long Non-coding Rnasmentioning
confidence: 99%
“…Luo et al screened lncRNA expression profiles in PE patients' placentas, suggesting abnormal lncRNA expression may be one of the causes of PE [8]. Based on this, Sun et al detected 5 known uterusrelated lncRNAs' expression in 48 PE patients and 24 non-PE healthy subjects and found lncRNA BC030099 expression was significantly facilitated, indicating elevated plasma level of lncRNA BC030099 is related to an accelerated risk of PE and can be used as the potential biomarker to predict the occurrence of PE [9], but whether it is involved in the disease progression of PE and its specific mechanism still need to be further explored.…”
Section: Introductionmentioning
confidence: 99%